Indonesian Political Economic Policy and Economic Rights: An Analysis of Human Rights in the International Economic Law (Journal of Private and Commercial Law, 2019)
The national and international economic development raises new problems besides the positive side of finance. International economic recession that has global impacts including in Indonesia presents its own challenges. One of the challenges faced is a serious impact on the fulfillment of economic and social rights. Various economic austerity measures were taken to maintain the country’s economic stability. One of the most controversial is the reduction of subsidies in the health, social security, trade and education sectors. The unemployment rate also increased as a direct impact of these economic policies. This paper analyzes the rights of human rights in Indonesian political economic policy both on a national and international scale. This paper compares and analyzes various cases of Indonesian economic policy with the basic principles of human rights, especially social, economic and cultural rights. Studies in this paper cover the areas of study of International Economic and Trade Law, Human Rights Law, and International Law. This paper highlighted that economic policies in the form of reducing subsidies and austerity measures undermine a wide range of human rights human rights frameworks.